2008
DOI: 10.1097/hjh.0b013e3282f283f3
|View full text |Cite
|
Sign up to set email alerts
|

Reninoma: case report and literature review

Abstract: Reninoma is a tumor of the renal juxtaglomerular cell apparatus that causes hypertension and hypokalemia via hypersecretion of renin. We describe a case of reninoma and provide a review of the literature, with a discussion emphasizing the diagnostic evaluation for such patients. The subject had persistent elevation of both plasma renin activity (PRA) and aldosterone. Imaging studies revealed the presence of a lesion in the renal cortex, which was further identified as a renin-producing lesion via selective ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
142
3
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(171 citation statements)
references
References 62 publications
15
142
3
11
Order By: Relevance
“…It has been reported that CT and MRI scans are useful for detecting the presence of JCT (9,(15)(16)(17)(18). However, in our case, the tumor was not detected on CT or MRI performed 10 years before the diagnosis.…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations
“…It has been reported that CT and MRI scans are useful for detecting the presence of JCT (9,(15)(16)(17)(18). However, in our case, the tumor was not detected on CT or MRI performed 10 years before the diagnosis.…”
Section: Discussioncontrasting
confidence: 48%
“…However, the clinical behavior of these lesions can be malignant as a result of severe systemic complications of hypertension. It has been reported that the prevalence of retinopathy, renal insufficiency and left ventricular hypertrophy in cases of JCT is 24%, 3% and 7%, respectively (9). However, in our case, most likely due to the patient's young age and well-controlled blood pressure (resulting from the use of antihypertensive medications), the organ damage was not detected.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…The most frequent histological type is renal juxta-glomerular apparatus tumor [4]. However, uterin leiomyosarcoma has already been described in a 60 y/o woman with hypertension and hypokaliemia [1].…”
Section: Case Reportmentioning
confidence: 99%